#151 Formulation and evaluation of floating tablets of Levofloxacin for eradication of Helicobacter pylori - K, Jaganathan; R, Sambathkumar; N, Venkateswaramurthy; M, Vijayabaskaran (Journal of Pharmaceutical Chemistry, 2022)
Helicobacter pylori (H. pylori) infection is a common worldwide infection and an important cause of peptic ulcer disease and gastric cancer. The purpose of the study was to prepare levofloxacin (LVF) floating tablets for Helicobacter pylori eradication. Floating tablets of Levofloxacin were prepared by direct compression using different hydrocolloid polymers such as hydroxypropyl methylcellulose (HPMCK4M, HPMCK100M) and natural polymers like xanthan gum, guar gum in an optimized ratio. The floating property was achieved using an effervescent mixture of sodium bicarbonate and citric acid (3:1). Hardness, friability, content uniformity, floating time, and floating lag time of the prepared floating tablets were evaluated. The Physical properties, drug content, floating time, and drug release behavior of prepared tablets was assessed. In-vitro results showed that Levofloxacin (LVF) floating tablet formulation composed of synthetic and natural gum shows a longer drug floating time character. The formulation contains both synthetic and natural gum shows a longer floating time (>12 h). From the study, it can be concluded that a combination of hydroxypropyl methylcellulose (HPMCK4M, HPMCK100M) along with natural polymers can be used to increase the gastric residence time of the dosage form to improve the local effect of Levofloxacin for the treatment of H. pylori infection.